what is -4 5/11 - 2 4/11

5 answers

To subtract these mixed numbers, we need to make sure that the fractions have the same denominator.

-4 5/11 = -4 + 5/11
-2 4/11 = -2 + 4/11

Now, we can subtract the whole numbers and the fractions separately:

-4 + (-2) = -6

5/11 - 4/11 = (5 - 4)/11 = 1/11

Therefore, -4 5/11 - 2 4/11 = -6 1/11.
-6 7/12 - 4 1/3
To subtract these mixed numbers, we need to make sure that the fractions have the same denominator.

-6 7/12 = -6 + 7/12
-4 1/3 = -4 + 1/3

Now, we can subtract the whole numbers and the fractions separately:

-6 + (-4) = -10

7/12 - 1/3 = (7/12) * (3/3) - (1/3) * (4/4) = 21/36 - 4/36 = 17/36

Therefore, -6 7/12 - 4 1/3 = -10 17/36.
simplify that
To simplify -10 17/36, we can rewrite it as an improper fraction.

-10 is equivalent to -10/1.

So, we have:

-10 17/36 = -10/1 + 17/36

To add these fractions, we need to have the same denominator. The easiest way is to find the least common multiple (LCM) of 1 and 36, which is 36.

-10/1 can be rewritten as -360/36, and 17/36 stays the same.

Now, we can add the fractions:

-360/36 + 17/36 = (-360 + 17)/36 = -343/36

Therefore, -10 17/36 simplified is -343/36.